PELATIHAN PLIOMETRIK DEPTH JUMP LEBIH MENINGKATKAN DAYA LEDAK OTOT TUNGKAI DARIPADA PELATIHAN PLIOMETRIK BOX JUMP SISWA PESERTA EKSTRAKURIKULER BOLA VOLI SMK NEGERI 1 PETANG - I Putu Prisa Jaya; Ketut Tirtayasa; I Made Muliarta; Luh Made Indah Sri Handari Adiputra; Susy Purnawati; I Putu Adiartha Griadhi (Sport and Fitness Journal, 2018)
ABSTRACTThe basic techniques of volleyball used to use muscular group in our body, especially the leg’s muscles that is facilitating the springboard movement. Explosive power is the ability of muscles to exert maximum force in a very quick time. Leg muscle explosive power is one of the essential components required in the sport of volleyball particular in the motion of smash, passing and blocking hat needs to be improved by training plyometrics. The training that were conducted during this research are the plyometric depth jump and plyometric box jump training using the principle of progressive load with 3 times frequencies a week within 6 weeks. The aim of this study is to compare the explosive power of training leg muscle. This study use a randomized experimental design with pre test and post test group design for six weeks with 3 times frequencies a week. The sample’s numbers is 32 participants that was divided into two groups. The first group was given training in plyometrics depth jump and the second group was given training plyometrics box jump. The explosive power of leg muscle is measured by using a jump DF which measured before and after training for each groups. The result of this research is shown before training in group I is 42.25 ± 3.92 cm and 51.81 ± 4.41cm after training (p <0.05). While, in group II the mean shows 40.25 ± 5.14 cm before training and 45.25 ± 5.07 cm after training (p <0.05). Training in group I can increase explosive power leg muscle than group II (p <0.05). Based on the result, it is concluded that the plyometric depth jump training is more better than the plyometric box jump training in increasing explosive power leg muscle for the students of volley ball extracurricular at SMK Negeri 1 Petang.Keywords: plyometrics depth jump training and box jump, explosive power leg muscle, sports volleyball.